2013
DOI: 10.1021/ja411050r
|View full text |Cite
|
Sign up to set email alerts
|

Facet-Selective Growth on Nanowires Yields Multi-Component Nanostructures and Photonic Devices

Abstract: Enhanced synthetic control of the morphology, crystal structure, and composition of nanostructures can drive advances in nanoscale devices. Axial and radial semiconductor nanowires are examples of nanostructures with one and two structural degrees of freedom, respectively, and their synthetically tuned and modulated properties have led to advances in nanotransistor, nanophotonic, and thermoelectric devices. Similarly, developing methods that allow for synthetic control of greater than two degrees of freedom co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 32 publications
(76 reference statements)
2
45
1
Order By: Relevance
“…The EDX map demonstrates the selective growth of InP shell, resulting in poor coverage of InP on the GaAs 0.56 Sb 0.44 core along the 〈112〉A directions. This facet‐selective growth has been demonstrated for radial inclusion of different quantum structures in both group IV and III–V semiconductor nanowire systems . Figure c compares the EDX spectrum of the core and shell.…”
Section: Resultsmentioning
confidence: 55%
“…The EDX map demonstrates the selective growth of InP shell, resulting in poor coverage of InP on the GaAs 0.56 Sb 0.44 core along the 〈112〉A directions. This facet‐selective growth has been demonstrated for radial inclusion of different quantum structures in both group IV and III–V semiconductor nanowire systems . Figure c compares the EDX spectrum of the core and shell.…”
Section: Resultsmentioning
confidence: 55%
“…9 These heterostructures can be grown either axially or radially based on the device requirements. 16 However, the unique prospect of selective radial heterostructure growth on the designed axial sections along the length of the nanowire is yet to be explored and employed in a device structure. It has also been demonstrated that radial growth can be tuned to be selective to certain nanowire facets.…”
Section: Introductionmentioning
confidence: 99%
“…However, for the core/shell nanowire structure, the critical thickness is larger than that of the planar growth, which reduces the burden in terms of the selection of the thickness and Ge fraction of the shell layer . Furthermore, conformal and either a single‐like or polycrystalline shell layer can be obtained by choosing the appropriate gas‐phase species, employing a vapor‐liquid‐solid chemical vapor deposition (VLSCVD), adopting the nucleation properties of Ge adatoms on the Si facets, and making the core structure similar to a circle . With respect to the gate stack, a Si‐capping layer and post‐deposition annealing (PDA) can be solutions for higher mobility and a reduced gate leakage current .…”
Section: Resultsmentioning
confidence: 99%